Waste Cellulose from Tetra Pak Packages as Reinforcement of Cement Concrete - Gonzalo Martínez-Barrera; Carlos E. Barrera-Díaz; Erick Cuevas-Yañez; Víctor Varela-Guerrero; Enrique Vigueras-Santiago; Liliana Ávila-Córdoba; Miguel Martínez-López (Advances in Materials Science and Engineering)
The development of the packaging industry has promoted indiscriminately the use of disposable packing as Tetra Pak, which after a very short useful life turns into garbage, helping to spoil the environment. One of the known processes that can be used for achievement of the compatibility between waste materials and the environment is the gamma radiation, which had proved to be a good tool for modification of physicochemical properties of materials. The aim of this work is to study the effects of waste cellulose from Tetra Pak packing and gamma radiation on the mechanical properties of cement concrete. Concrete specimens were elaborated with waste cellulose at concentrations of 3, 5, and 7 wt% and irradiated at 200, 250, and 300 kGy of gamma dose. The results show highest improvement on the mechanical properties for concrete with 3 wt% of waste cellulose and irradiated at 300 kGy; such improvements were related with the surface morphology of fracture zones of cement concrete observed by SEM microscopy.